(untitled) (International Journal of Technology and Management Research, 2022)
The construction sector differs from other industries as a result of its extraordinary attributes. Besides, every infrastructure project comprises diverse professionals and firms that meet up to accomplish explicit undertaking within a specified period. Leadership could increase productivity in construction project delivery, where competence, success, and additional work is expected to be part of the result. This research sought to assess the leadership styles of Ghanaian Construction Project Managers- CPMs in comparison with those of their expatriate (foreign construction project managers) counterparts by means of Fielder’s Least Preferred Co- manager worker (LPC) scale. Twenty (20) Ghanaian CPMs as well as twenty (20) expatriate CPMs were selected, but in total, thirty (31) CPMs participated in this study. Findings from the research indicated that, the Ghanaian CPM were found to be relationshiporiented than their foreign counterparts. The foreign CPM were found to be more socio-independent. Further findings on the actual leadership style of the CPMs showed no major leadership style within the construction space in Ghana, although the participative and directive styles were increasingly common. The result implies that though the leadership style of both respondents is different, the difference is not significant.